Development of Soil Wetting Front Estimation Models in Sandy Soil with a Hard Pan Under Drip Irrigation Using Empirical and Response Surface Methodologies - Oluwaseun Temitope Faloye; Amanda Ezeh; Viroon Kamchoom; Oluwaseyi Matthew Abioye; Peter Pelumi Ikubanni (My University, 2025)
An accurate estimation of a soil wetting front is important for improving water-use efficiency under drip irrigation. This study is aimed at determining the wetting front of sandy soil under drip irrigation using the existing and modified empirical equations and optimizing the input parameters using the response surface methodology (RSM). This study was conducted during the dry season in sandy soil containing a hard pan at a soil depth of about 30 cm. The soil wetting front was measured using measuring tape at two emitter discharges under a point-source drip irrigation system type. An evaluation of the models for the wetting fronts during calibration and validation showed that the coefficient determination (r2) ranged between 77–98% and 79–99% for the empirical and modified models, respectively. The normalized root mean square error (NRMSE) was less than 20% and greater than 20% for the modified and existing equations, respectively, thus emphasizing that the modified model produced a better result. Using the RSM approach, the linear + interaction produced the best result, and the optimization result revealed an optimum irrigation time and volume of 75 min and 225 cm3, corresponding to a maximum wetting depth and width of 26.8 and 21.7 cm, respectively.
Keywords: Soil and Unsaturated Flow